To determine which of the given functions is an odd function, we need to recall the definition of an odd function. A function \(f(x)\) is considered odd if it satisfies the condition:
\[ f(-x) = -f(x) \]
for all \(x\) in its domain.
Let's analyze each function:
-
\(f(x) = x^4\):
- \(f(-x) = (-x)^4 = x^4\)
- Since \(f(-x) = f(x)\), this function is even.
-
\(f(x) = 3x^2\):
- \(f(-x) = 3(-x)^2 = 3x^2\)
- Since \(f(-x) = f(x)\), this function is even.
-
\(f(x) = 2x^3\):
- \(f(-x) = 2(-x)^3 = -2x^3\)
- Since \(f(-x) = -f(x)\), this function is odd.
-
\(f(x) = 2(x+1)^3\):
- \(f(-x) = 2(-x + 1)^3 = 2(1 - x)^3\), which does not simplify to \(-f(x)\).
- Therefore, this function is neither odd nor even.
Based on this analysis, the odd function among the options is:
\(f(x) = 2x^3\).